The effect of real earnings management on auditing fees in listed companies in Tehran Stock Exchange - Mohammad Shameli Shahreza; Hassan Ghodrati (Management Science Letters)
This study aims to determine the relationship between the capital structure and economic value added. In this context, the rates of total debt to total asset, total current debt to total asset, total long debt to total asset and total debt to total equity are distinguished as the measures of capital structure. The data used in this study consisted of a sample of 133 companies listed in Tehran Stock Exchange from 2008 to 2012. To analyze the data and to perform hypothesis tests, a linear regression model, based on combinatorial methods or data panel, and also a nonparametric Spearman correlation analysis have been applied. The results of the research hypothesis tests based on regression analysis revealed an insignificant relationship between capital structure and economic value added. Furthermore, the results showed that, there was an inverse moderate relationship between rate of total debt to total asset and total current debt to total asset with economic value added. There is an inverse weak relationship between rate of total long debt to total asset and total debt to total equity with economic value added.